2015
DOI: 10.3892/mmr.2015.4750
|View full text |Cite
|
Sign up to set email alerts
|

TRPC6 is required for hypoxia-induced basal intracellular calcium concentration elevation, and for the proliferation and migration of rat distal pulmonary venous smooth muscle cells

Abstract: Hypoxia induces pulmonary vasoconstriction and reconstruction in the pulmonary arteries and pulmonary veins (PVs), and elevation of intracellular calcium concentration ([Ca2+]i) is a primary factor of these processes. In the present study, the role of transient receptor potential cation channels (TRPCs) in mediating the hypoxia-induced elevation of [Ca2+]i in rat distal pulmonary venous smooth muscle cells (PVSMCs) was investigated. Rats with chronic hypoxic pulmonary hypertension (CHPH) were used for in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…To the best of our knowledge, this is the first study regarding the importance of TRPC6 in HBSMC proliferation. Recent studies also have suggested a key role of TRPC6 calcium entry in the mediation of [Ca 2+ ] i elevation and cell proliferation [61, 62]. Based on the observations from this study, the attenuation of SOCE and ROCE may serve as a potential therapeutic approach for COPD.…”
Section: Discussionmentioning
confidence: 89%
“…To the best of our knowledge, this is the first study regarding the importance of TRPC6 in HBSMC proliferation. Recent studies also have suggested a key role of TRPC6 calcium entry in the mediation of [Ca 2+ ] i elevation and cell proliferation [61, 62]. Based on the observations from this study, the attenuation of SOCE and ROCE may serve as a potential therapeutic approach for COPD.…”
Section: Discussionmentioning
confidence: 89%
“…Here we show that the contractile effect of PDGF-BB also depends on it. Increased calcium-levels represent a major trigger for vasoconstriction, proliferation and migration of vascular SMCs [ 18 , 80 , 125 127 ]. Thus, stimuli which increase calcium-levels, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, stimuli which increase calcium-levels, e.g. TXA 2 or ET-1 [ 80 , 128 ], but also hypoxia [ 125 , 127 ] or PDGF-BB [ 2 , 64 ] do not constrain to increase the pulmonary vascular tone, but also promote pulmonary vascular remodelling. Hence, enhanced tone and remodelling are closely linked with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Expressed by smooth muscle cells, Trpc6 has been shown to be a major constituent of agonist-induced receptor-operated calcium entry in systemic and pulmonary artery smooth muscle cells [4749]. Enhanced expression of Trpcs , including Trpc6 , plays a critical role in the increase of pulmonary vascular tone in experimental model of pulmonary hypertension induced by chronic hypoxia exposure [49, 50]. …”
Section: Discussionmentioning
confidence: 99%